2014
DOI: 10.1007/s10518-014-9695-9
|View full text |Cite
|
Sign up to set email alerts
|

Limit states of modern unreinforced clay brick masonry walls subjected to in-plane loading

Abstract: Recent research showed that the in-plane horizontal displacement capacity of unreinforced masonry (URM) walls depends on numerous factors that are not yet captured by current empirical drift capacity models; e.g., axial stress, shear span, geometry of the walls and the material used. In order to improve the performance-based assessment of URM wall buildings, future research should aim at developing numerical and mechanical models that link the global force-displacement response of URM walls to local deformatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 17 publications
(26 reference statements)
0
14
0
Order By: Relevance
“…assumption only holds as long as no significant diagonal crack separates the walls [20]; this limits the application of the model to walls with a dominating flexural mode. For determining the displacement capacity of flexure-dominated URM walls, local LSs need to be predicted as well as their influence on the kinematics of the wall implemented in the model from Section 3.…”
Section: Implementation Of Local Limit States In the Global Force-dismentioning
confidence: 99%
See 3 more Smart Citations
“…assumption only holds as long as no significant diagonal crack separates the walls [20]; this limits the application of the model to walls with a dominating flexural mode. For determining the displacement capacity of flexure-dominated URM walls, local LSs need to be predicted as well as their influence on the kinematics of the wall implemented in the model from Section 3.…”
Section: Implementation Of Local Limit States In the Global Force-dismentioning
confidence: 99%
“…Experiments showed that walls do not reach lateral load failure with the occurrence of first splitting cracks (LS-F3) but that at this instant, the walls are still able to sustain the applied lateral load and that the load can even increase slightly until first parts of the compression zone break completely apart (LS-F4, [20]). Figure 6 shows the crack pattern in the compression zone just after reaching LS-F3 (Figure 6(a)) and just before LS-F4 occurred (Figure 6(b)).…”
Section: Loss Of Part Of the Toe Region Due To Crushing (Ls-f4)mentioning
confidence: 99%
See 2 more Smart Citations
“…Penna (2015) discusses in his contribution several aspects of the seismic response and capacity of stone masonry buildings. By the evaluation of experimental results Petry and Beyer (2015) address the horizontal in-plane …”
mentioning
confidence: 99%